DEMOGRAPHIC FACTORS OF THE FISH TRADERS THAT AFFECTS THE ENVIRONMENTAL SITUATION OF THE FISH MARKET - Maina, Mwangi Albert; Kerich, Dr. Richard; Aloo, Dr. Theresa (International Journal of Environmental Sciences, 2016)
Purpose: The purpose of the study was to identify demographic factors of the fish traders affecting the environmental situation of the fish market. Methodology: A descriptive survey design was used for the research.The target for the study was the fish traders of Gikomba fish market, Nairobi. Random sampling of fish traders was done from a register, using Fischer's formulae, to calculate the number of respondents. Data was collected through a structured questionnaire and was processed using EXCEL and SPSS software packages. Descriptive statistics (frequencies, percentages,) and inferential statistics (Chi square and Logistic Regression) were used to explain the variables. 54% of the respondents did not get piped water. Results: Majority (60.5%) of the respondents noted that fish wastes had a negative effect on the environment.Chi squaretests results for fish operator practices in most attributes was statistically associated with environmental situation (P< 0.05).Logistic regression tests results proved that practices such as use of water, disposal of wastes, use of protective clothing and participation in cleanups had a statistically significant influence on the environmental situation (P< 0.05). Unique contribution to theory, practice and policy: The research recommended that the Department of Fisheries needs to review the modalities for fish handling throughout the marketing chain. Emphasis should be put on disposal of fish wastes in the major fish markets, fish wastes recycling options, training of fish operators and capacity development of staff.